Pengukuran Sudut Rancangan Penggerak Tempat Solar Cell Berbasis Motor Servo Menggunakan Sensor MMA8451 Dan Busur Derajat - Muhammad Rafly; Endang Iriawan; Elda Rayhana (Institut Sains dan Teknologi Nasional, 2024)
Abstract Solar cell is a potential new electrical energy developed in our country, but the current optimization is not optimal, one of which is due to static installation. In this study, a servo motor was used to drive the solar cell based on the angle of the sun, the ESP32 microcontroller as the control brain, and the GY-45 MMA8451 accelerometer sensor and the protractor as the angle meter of the solar cell holder. From the measurement results, it is found that the angle value of the servo motor with a protractor is not the same, there is a difference in numbers from 5° to 20°, while the angle value of the GY-45 MMA8451 fluctuates and varies. From the research results, it is necessary to calibrate the code on the Arduino with the actual angle and the GY-45 MMA8451 sensor is generally very sensitive and susceptible to vibration. Keywords: Servo motor, Protractor, accelerometer sensor GY-45 MMA8451